Introduction to the history of printing in Guipúzcoa (1585-1850) - Fernández de Casadevante Romaní, Mª Dolores (Revista General de Información y Documentación, 2012)
This article reviews the history of the printers Guipúzcoa from 1585 to 1850. Who were the first printers who settled in Guipúzcoa and under what conditions, which process was followed in order to be official printer of the province, how their workshops were, etc.. In other provinces the printing was born thanks to college and therefore greater demand, while in Gipuzcoa was established to work primarily for the council, but could accept other jobs. From Peter of Burgundy even Baroja and Zuazua have shaped the history of printing and know their printed works, which are part of the bibliographic heritage of Guipúzcoa. Data were sought about their lives and works in archives, has expanded and corrected the information that existed until now and in some cases, have provided new data.
Keywords: Printing in Guipúzcoa; Guipuzcoan workshops; provincial Council of Guipúzcoa.